"Error But Without Malice" in Defamation of Public Officials: The Value of Free Expression in International Human Rights Law. Issue 3 (2nd July 2016) - Carter, Edward L.
Abstract : Government officials in various parts of the world use defamation to silence critics, but defamation liability may curtail freedom of expression on topics of public interest and undermine human rights generally. Article 19 of the International Covenant on Civil and Political Rights guarantees freedom of expression unless a state can show need to protect individual reputation and acts proportionally. In its adjudication of complaints for violations of Article 19, and in its General Comment 34, the United Nations Human Rights Committee has crafted the principle that defamation liability may not be imposed if an erroneous statement about a public official was made in "error but without malice." Although soft law, General Comment 34 represents the committee's most compelling articulation of the values animating freedom of expression in international human rights law, and chief among the values is the role played by free expression to promote realization of all human rights.